Kebiasaan yang Menjadi Hukum Adat Lintas Keluarga (Studi Kasus Kunjungan Setiap Hari Raya Besar antar Umat Beragama di Sulawesi Utara) - Rumondor, Prasetio; Tumiwa, Anisa Jihan (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2019)
The Purpose of writing this articles is to find out the interactions and habits of the people on major holidays between religious communities in North Sulawesi. This study uses qualitative research methods, with data collection techniques based on observations, interviews and documentation studies, as well as sociological approaches with studies cross-sectional. The results of this study show that interfaith visits, especially by each family, are still strongly bound by kinship but have distance and boundaries from each religion. Then, there are legal causes and legal consequences that occur from customary law visit when religious feast day are smaller in scope, namely the family which will automatically influence the interaction of the people of North Sulawesi.